A Rhetorical Analysis of RM's Speech at the United Nations General Assembly and Its Application in Teaching Speaking - Atika Ariyanti; Sudar Sudar; Tusino Tusino (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
This study aims to find out rhetorical proof and rhetorical figure of repetition, to analyze the speech delivery strategy, and to explain the application of rhetoric in teaching speaking. This research belongs to qualitative research. The main instrument in this research was the researcher itself using documentation. The data of this research was taken from RM’s speech at the United Nations General Assembly in the form text and video. The unit analysis of this research was the transcript of RM’s speech and the video of the speech. The researcher analyzed the data using content analysis. The result of this research showed that RM used rhetorical proof logos (10%), ethos (42%), and pathos (48%) in his speech. He also provided rhetorical figure of repetition such as anaphora (45%), epistrophe (11%), mesodiplosis (22%), anadiplosis (11%), and conduplication (11%) to give his speech the touch of art. In delivering speech, he used speech delivery strategy, includes storytelling for 54%, tone of voice, pause, and body movement. Moreover, the result of the study in this research can be applied in English learning at the tenth grade, especially in spoken advertisement.